Amb una rosa a la galta - «Ball de la Mare de Déu» (1788) de fra Josep Rius i «Isabet Besora, la pastoreta» de Pere Gras i Bellvé (1857). - KOVÁCS, LENKE (Scripta, 2023)
In this article we present a comparative study of two Marian plays from the late 18th and mid-19th centuries. The Ball de la Mare de Déu, written by the Franciscan Josep Rius and premiered in 1788, belongs to the genre of ball parlat, a form of popular theatre performed outdoors that combines theatrical dialogue with music and dance. The play Isabet Besora, la pastoreta ó ja sía la peste de Reus de 1592 by Pere Gras i Bellvé, published in 1857, is a historical drama in three acts on the same theme that was premiered in 1860 at the Teatre Principal in Reus. In addition to the study, we offer a new edition of the play by Rius based on the unique manuscript in which the text has come down to us and which is kept in the Arxiu Museu de Reus with the signature FDIMMR 10.6.